Hubungan Derajat Perdarahan Intra Operasi Dengan Kejadian Shivering Pasca Operasi Pada Pasien Spinal Anestesi: Hubungan Derajat Perdarahan Intra Operasi Dengan Kejadian Shivering Pasca Operasi Pada Pasien Spinal Anestesi - Shefi Salsabila; Dyah Restuning Prihati; Heny Prasetyorini (Jurnal Keperawatan Terapan, 2026)
Postoperative shivering is a common complication in patients undergoing spinal anesthesia and may increase oxygen consumption, cardiac workload, and delay recovery. Intraoperative bleeding is considered one contributing factor, as blood loss can reduce core body temperature. This quantitative correlational study used a cross-sectional approach involving 76 patients selected through purposive sampling. Intraoperative bleeding was assessed using observation sheets, while shivering was measured using a standardized shivering scale. Data were analyzed using the Spearman Rank test. Most respondents experienced mild shivering (57.9%) and Class 1 intraoperative bleeding (78.9%). Statistical analysis showed a p-value of 0.000 and an r-value of 0.440, indicating a significant moderate positive correlation. Higher degrees of intraoperative bleeding are associated with an increased risk of postoperative shivering in spinal anesthesia patients.